Synthesis, Characterization, and Theoretical Calculation of New Azo Dyes Derived from [1,5‐a]Pyrimidine‐5‐one Having Solvatochromic Properties - Şener, Nesrin; Gür, Mahmut; Çavuş, M. Serdar; Zurnaci, Merve; Şener, İzzet (Wiley, 2019)
7‐Amino‐3‐phenylazo‐2‐methyl‐4H‐pyrazolo[1,5‐a]pyrimidine‐5‐one (3) was synthesized by the reaction of 5‐amino‐3‐methyl‐4‐phenylazo‐1H‐pyrazole and 2‐aminobenzothiazole with ethyl cyanoacetate in acetic acid at 150°C. Four novel heterocyclic azo disperse dyes were obtained by the coupling of heterocyclic amines‐based diazonium chloride with compound 3. They were purified and characterized by elemental analysis, FTIR, and 1H NMR. Furthermore, solvatochromic behaviors of related dyes were studied in detail by using ultraviolet–visible absorption spectrometer. The experimental data were supported by density functional theory using b3lyp/cc‐pvtz level calculations, and a detailed analysis of predicted tautomeric structures was made.